2020
DOI: 10.1002/stem.3204
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miRNA-17-5p derived from human umbilical cord mesenchymal stem cells improves ovarian function in premature ovarian insufficiency by regulating SIRT7

Abstract: Premature ovarian insufficiency (POI) is clinically irreversible in women aged over 40 years. Although numerous studies have demonstrated satisfactory outcomes of mesenchymal stem cell therapy, the underlying therapeutic mechanism remains unclear. Exosomes were collected from the culture medium of human umbilical cord mesenchymal stem cells (hUMSCs) and assessed by electron microscopy and Western blot (WB) analysis. Then, exosomes were added to the culture medium of cyclophosphamide (CTX)‐damaged human granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 52 publications
3
52
0
Order By: Relevance
“…6 a) while it repressed apoptosis in granulosa, theca, and stromal cells (Fig. 5 ), demonstrating that hAMSCs might also promote oocyte maturation by improving ovarian microenvironment, consistent with previous reports [ 24 , 25 , 29 , 30 ]. Besides, serum hormone levels of AR-DOR mice were somehow rebalanced (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…6 a) while it repressed apoptosis in granulosa, theca, and stromal cells (Fig. 5 ), demonstrating that hAMSCs might also promote oocyte maturation by improving ovarian microenvironment, consistent with previous reports [ 24 , 25 , 29 , 30 ]. Besides, serum hormone levels of AR-DOR mice were somehow rebalanced (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, it is reported that transplantation of UCMSC functions on POI patient [ 23 ]. Further explorations demonstrate that MSCs improved ovarian function through oxidation resistance in which PI3K-FoxO3a or SIRT signal pathway is involved [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…6a) meanwhile repressed apoptosis in granulosa and stromal cells (Fig. 5), demonstrating that hAMSCs might also promote oocyte maturation by improving ovarian microenvironment, consistent with previous reports [24,25,29,30]. Besides, serum hormone levels of AR-DOR mice were rebalanced (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…3c, d), meaning that they functioned by secreting cytokines [63] (Fig. 1b) and/or vesicles [24,29] rather than differentiation into tissue-speci c cells. That precise hAMSCs-secreting components effective in ovarian function repairability and the function mechanism would be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation